Ecological risk assessment of aquatic organisms induced by heavy metals in the estuarine waters of the Pearl River - Tang, Zhihua; Liu, Xinyu; Niu, Xiaojun; Yin, Hua; Liu, Minru; Zhang, Dongqing; Guo, Huafang (Scientific reports, 2023)
With the rapid economic development of China's coastal areas and the growth of industry and population, the problem of heavy metal contamination in estuarine waters is increasing in sensitivity and seriousness. In order to accurately and quantitatively describe the current status of heavy metal contamination and identify sensitive aquatic organisms with high ecological risks, five heavy metals in eight estuaries of the Pearl River were monitored at monthly intervals from January to December in 2020, and the ecological risks of aquatic organisms induced by heavy metals were evaluated using Risk quotients (RQ) and species sensitivity distributions (SSD) methods. The results showed that the concentrations of As, Cu, Pb, Hg and Zn in estuaries of the Pearl River were (0.65–9.25) μg/L, (0.07–11.57) μg/L, (0.05–9.09) μg/L, (< 0.40) μg/L and (0.67–86.12) μg/L, respectively. With the exception of Hg in Jiaomen water, the other heavy metals in each sampling site met or exceed the water quality standard of Grade II. The aquatic ecological risks of As, Pb and Hg were generally low in the waters of the Pearl River estuary, but individual aquatic organisms are subject to elevated ecological risks due to Cu and Zn. The content of Zn has a lethal effect on the crustaceans Temora Stylifera , and the content of Cu has a serious impact on the mollusks Corbicula Fluminea and has a certain impact on the crustaceans Corophium sp. and the fish Sparus aurata . Heavy metal levels and joint ecological risks (msPAF) in the Humen, Jiaomen, Hongqimen, and Hengmen estuaries were slightly higher than in other estuaries, and the Yamen estuary had the lowest contration of heavy metals and ecological risk. Research findings can serve as a basis for formulating water quality standards for heavy metals and for protecting aquatic biodiversity in the Pearl River Estuary.